Robust and universal seamless handover authentication in 5G HetNets - ZHANG, Yinghui (Institutional Knowledge at Singapore Management University, 2021)
The evolving fifth generation (5G) cellular networks will be a collection of heterogeneous and backward-compatible networks. With the increased heterogeneity and densification of 5G heterogeneous networks (HetNets), it is important to ensure security and efficiency of frequent handovers in 5G wireless roaming environments. However, existing handover authentication mechanisms still have challenging issues, such as anonymity, robust traceability and universality. In this paper, we address these issues by introducing RUSH, a Robust and Universal Seamless Handover authentication protocol for 5G HetNets. In RUSH, anonymous mutual authentication with key agreement is enabled for handovers by exploiting the trapdoor collision property of chameleon hash functions and the tamper-resistance of blockchains. RUSH achieves universal handover authentication for all the diverse mobility scenarios, as exemplified by the handover between 5G new radio and non-3GPP access regardless of the trustworthiness of non-3GPP access and the consistency of the core network. RUSH also achieves perfect forward secrecy, master key forward secrecy, known randomness secrecy, key escrow freeness and robust traceability. Our formal security proofs based on the BAN-logic and formal verification based on AVISPA indicate that RUSH resists various attacks. Comprehensive performance evaluation and comparisons show that RUSH outperforms other schemes in both computation and communication efficiencies.